Hubungan Antara Dukungan Sosial Teman Sebaya Dengan Stres Akademik Pada Mahasiswa Yang Bekerja - A, Asfinolia; Razak, Ahmad; Halima, Andi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine the relationship between peer social support and academic stress in working students. The respondents in this research were 100 students who worked in Makassar City. Data collection was carried out using a Likert scale, namely the peer social support scale and the academic stress scale. Hypothesis testing used Spearman Rank correlation analysis with the help of SPSS 25. The results showed that there was a relationship between social support from peers and academic stress in working students with a significance value of 0.006 < 0.05. This means that the higher the social support from peers, the lower the academic stress for working students.